2016
DOI: 10.1038/srep28642
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of mechanical nociception differs in the adult and infant brain

Abstract: Newborn human infants display robust pain behaviour and specific cortical activity following noxious skin stimulation, but it is not known whether brain processing of nociceptive information differs in infants and adults. Imaging studies have emphasised the overlap between infant and adult brain connectome architecture, but electrophysiological analysis of infant brain nociceptive networks can provide further understanding of the functional postnatal development of pain perception. Here we hypothesise that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 65 publications
6
51
0
Order By: Relevance
“…We found the NPS to be expressed similarly across infants and adults. This result aligns with a recent EEG study comparing pain responses of adults and infants 36 . Here, infants displayed noxious evoked potentials and gamma oscillations, understood in adults to be markers of primary nociceptive processing and subjective pain 47 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found the NPS to be expressed similarly across infants and adults. This result aligns with a recent EEG study comparing pain responses of adults and infants 36 . Here, infants displayed noxious evoked potentials and gamma oscillations, understood in adults to be markers of primary nociceptive processing and subjective pain 47 .…”
Section: Discussionsupporting
confidence: 92%
“…In infants, noxious-evoked behaviour and brain activity have been studied and correlated 3436 . However, determining a quantitative association between behaviour, or brain activity, and perception has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scalp EEG recording in preterm human infants has demonstrated that clinically required noxious skin stimulation evokes specific nociceptive ERPs from 30 to 35 gestational weeks onwards gradually replacing the immature nonspecific burst responses (Fabrizi et al 2011). Time frequency analysis of cortical activity in full-term infants shows that nociceptive stimuli are encoded differently from that in adults (Fabrizi et al 2016) but more research is required to understand the maturation of pain representation in the human infant brain. Oscillations and their synchronization are important correlates of neuronal processing, and coordination of neural activity into whole-brain functional networks can provide valuable measures for the assessment of brain functions.…”
Section: Discussionmentioning
confidence: 99%
“…The current view of pain is that it arises from a distributed network of brain activity, none of which is unique to pain, but when coordinated or synchronized, results in the sensory, emotional, motivational, and cognitive experience that is pain56. Therefore, non-intervened pain, particularly that which occurs during a critical period of brain development, can cause long-term behavioral alteration in humans and animals789.…”
mentioning
confidence: 99%